1960
DOI: 10.2136/sssaj1960.03615995002400020017x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long‐Time Fertility Management Practices on Chemical and Physical Properties of a Fargo Clay

Abstract: Laboratory phases of a study to evaluate the effectiveness of various long‐time management practices in maintaining fertility of Fargo clay are reported. Soil samples which had been taken at the beginning of the trial in 1913 and those taken in 1952 and 1953 were used for chemical analyses. Physical measurements were made on samples taken from 1954 to 1956. Analyses included total N, organic C, pH, cation‐exchange capacity, exchangeable cations, extractable and organic P, nitrification capacity, aggregation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…S ince virgin soils of the Great Plains were put under cultivation, their productivity has decreased as a consequence of organic matter losses associated with extensive tillage and extended summer fallow periods. Research has shown that soil C and N levels decline with years of cultivation (Haas et al, 1957; Young et al, 1960; Tiessen et al, 1982) and that this tendency can be minimized or eliminated by converting to soil conservation practices such as no‐till or stubble mulch (Dick, 1983; Lamb et al, 1985). Conversion to no‐till or stubble mulch practices also greatly influences physical, chemical, and microbiological properties of the soil (Lamb et al, 1985; Mielke and Wilhelm, 1998).…”
mentioning
confidence: 99%
“…S ince virgin soils of the Great Plains were put under cultivation, their productivity has decreased as a consequence of organic matter losses associated with extensive tillage and extended summer fallow periods. Research has shown that soil C and N levels decline with years of cultivation (Haas et al, 1957; Young et al, 1960; Tiessen et al, 1982) and that this tendency can be minimized or eliminated by converting to soil conservation practices such as no‐till or stubble mulch (Dick, 1983; Lamb et al, 1985). Conversion to no‐till or stubble mulch practices also greatly influences physical, chemical, and microbiological properties of the soil (Lamb et al, 1985; Mielke and Wilhelm, 1998).…”
mentioning
confidence: 99%
“…1980) . Young et al (1960) reported that no P applications for 40 years caused an appreciable loss of P. A relation ship between an increase in the soil P content and the soil P content existing at the beginning of the experiment was detected in plots treated with P every four years (Young et al, 1960). The soil P content increased with any treatment of P for 38 years in comparison with the check in a four-year rotation (Riddley and Hedlin, 1962).…”
Section: Influence Of Past Fertilizer-p Applications On the Availabilmentioning
confidence: 97%
“…Some researchers (Klute & Jacob, 1949;Young et al, 1960;McIntosh and Varney, 1973) have reported no direct benefit of manure on soil physical properties, and attribute improved crop performance to nutrients in the manure (Aoda et al, 1987). Other authors (Arriaga and Lowery, 2003;Bulluck et al, 2002) attribute significant changes in soil structure to manure application.…”
Section: Manure and Compost Applicationmentioning
confidence: 99%